2012
DOI: 10.4236/ajps.2012.34051
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate Biofertilizer, Row Spacing and Plant Density Effects on Corn (<i>Zea mays</i> L.) Yield and Weed Growth

Abstract: A field study was conducted at the Agricultural Research Farm of Razi University, Kermanshah, Iran to investigate the effects of phosphate biofertilizer, row spacing and plant density on corn yield and weed growth. The experiment was a factorial with three factors arranged in a randomized complete block design with three replications. The first factor was phosphate biofertilizer (inoculation and non-inoculation), the second was row spacing (conventional (75 cm) and reduced (50 cm)) and the third was plant dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 21 publications
3
19
0
1
Order By: Relevance
“…Barvar-2 contains phosphate-solubizing microorganisms such as Bacillus lentus and Pseudomonas putida. It is proposed that these phosphorus biofertilizers can replace traditional P fertilizers as they have the ability to dissolve calcium phosphate and apatite associated with plant roots (Mohammadi et al, 2012).…”
Section: Mineral Fertilization and Biofertilization Differentially Afmentioning
confidence: 99%
“…Barvar-2 contains phosphate-solubizing microorganisms such as Bacillus lentus and Pseudomonas putida. It is proposed that these phosphorus biofertilizers can replace traditional P fertilizers as they have the ability to dissolve calcium phosphate and apatite associated with plant roots (Mohammadi et al, 2012).…”
Section: Mineral Fertilization and Biofertilization Differentially Afmentioning
confidence: 99%
“…Row spacing and spatial uniformity can play important roles to manage weeds in cropping systems. Mohammadi et al (2012) reported that corn yield was improved and weed biomass was decreased in response to decreasing row spacing. Moreover a more uniform crop spatial (as seen at the P2 planting arrangement) decreases competition within the crop population early in the growing season (Olsen and Weiner 2007) and maximizes the total shade cast by the crop by reducing self shading (Weiner et al 2001).…”
Section: Resultsmentioning
confidence: 99%
“…In another study, Mohammadi et al (2012) found that both crop yield and weed control can be improved by increasing the planting spatial uniformity in a corn cropping system.…”
Section: Resultsmentioning
confidence: 99%
“…The positive influence of the narrower line Figure 8. Dependency of the proportion of the aerial precipitation (P, mm) and throughfall (P th , mm) on the calculated values of the leaf area index (LAI cal ); values of LAI cal and P/P th used in the models were derived from the periods when the plants were within the phase BBCH 30-70; data from years 2012-2014; r -correlation coefficient; *confidence level 95.0% on the elimination of erosion processes was also determined, due to the estimation of lower MSR values on the 0.45 m wide compared with the 0.75 m wide rows (Uppenkamp 2007;Nübel 2008;Mohammadi et al 2012). It is explainable by probably higher soil coverage by the leaves and by a greater proportion of stem flow (Bui & Box 1992;Zábranský et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, it is believed that reducing the maize lines width contributes to water erosion risk reduction (Uppenkamp 2007;Nübel 2008;Mohammadi et al 2012). In Germany, crops grown in row spacings ≤ 0.45 m, including maize, are not considered as wide-row crops.…”
mentioning
confidence: 99%